IMPLEMENTASI KEBIJAKAN PELAYANAN PERIZINAN PENANAMAN MODAL PADA BADAN PELAYANAN DAN PERIZINAN TERPADU KOTA PALU - Rosna, Rosna (Katalogis, 2015)
The Implementation of Investment Licensing Services Policy at Integrated Licensing Service Agency, Palu has not run optimally It is caused by 4 main factors, they are communication, res Keywords: Evaluation of the National Sports System, Human Resources .Disposition, and bureaucracy structure that have not run effectively yet the implementation, supporting means like human resource is limited. This research aims at analyzing the policy of investment licensing service as resource, disposition, and bureaucracy structure. The method used in this research is qualitative with 5 informants taken by using purposive sampling technique. The data was collected by interview and documentation study and then analyzed with interactive method. This research results (1) Communication; socialization to society was still limited (2) Resource; the limited employees that comprehend service and licensing rules, the lack of self development professionally, limitation of operational service vehicles (3) Disposition; although BP2T has shown a quality of services, but it is constrained in investment sector at Regional Planning and Investment Agency (4) Bureaucracy structure; at Licensing and Service Agency of Palu City, so far has run as the procedures. It is proven by the existence of tasks rationing at each sector and based on SOP, and the responsible employees of Integrated Licensing Service Agency in carrying out public services.